Mulur Mungkret: Ilmu Bahagia Suryomentaram sebagai Etika Ekologi Nusantara - Gerardus Chrisdinando OCarm; Armada Riyanto; Mathias Jebaru Adon (Yayasan Ekologi Masyarakat dan Sains, 2026)
Modern Environmental Ethics is facing with the fact that nature is being destroyed. The cause is none other than the post-modernist mentality, which views the environment as merely a means to fulfill human needs. Some cultural problems: 1) environmental ethics that emerged from the Western economic system is not in accordance with the mentality of East; 2) there is a movement to raise local wisdom as the basis of environmental ethics that are appropriate for certain localities. Suryomentaram's teachings succeeded in exploring the structure of the Nusantara's human psyche, with the finding that a fulfilled desire can mulur and mungkret causing a dynamic of feelings in every human being (raos sami). Raos sami is used as a benchmark to achieve a state of serene paradise, where everything done is free from the desire to mulur which causes distress. The concept of mulur mungkret can be applied as the basis of the Environmental Ethics of the Nusantara, which is in accordance with the temperament of the people, and in harmony with the cosmological concept of the Nusantara which emphasizes symbiotic mutualism between humans and nature.